The Effectiveness of Using Song Theraphy ?n Increasing Year 5 Primary Pupils’ Engagement ?n Science Classroom - Mai, Mohammed Yousef (European Journal of Multidisciplinary Studies, 2017)
The purpose of this study is to investigate the effectiveness of song theraphy in increasing students engagement in Science classroom. The researcher used questionnaire on students engagement items to analyze students level of engagement after using song theraphy in teaching science. The questionnaire has three sub categories, (1) cognitive engagement, (2) affective engagement and (3) behavioral engagement. The participants are total of 82 students from both controlled group (38.1 percent males and 61.9 percent females) and experimental group (45.0 percent males and 55.0 percent females). The data were analyzed using both descriptive (mean, frequency and percentage) and inference (Independent sample t-test, paired sample t-test and Kruskal-Wallis). The findings showed that students engagement after using song therapy is higher than before using it between the pretest and posttest for experimental group. Besides that, students’ engagement has increased after using song therapy to experimental group students compared to without using it to controlled group. Moreover, the mean between gender female and male is not much difference and not significant in comparing gender on the effectiveness of using song therapy for experimental group. In addition, the findings showed that the students level of engagement in Science classroom after the posttest is not effected by their level of achievement in Science test.